2022
DOI: 10.3390/antiox11112231
|View full text |Cite
|
Sign up to set email alerts
|

High-Yield Recovery of Antioxidant Compounds from Bambusa chungii Culms Using Pressurized Hot Water Extraction

Abstract: A large amount of waste from Bambusa chungii culms is generated from the bamboo pulping industry, causing disposal problems. Nevertheless, bamboo culms are a suitable source of functional ingredients, such as antioxidant compounds. However, because of the high compactness and tightness in their material structure, obtaining phytochemicals from bamboo culms using conventional organic solvent extraction methods can be inefficient. In this research, we developed a pressurized hot water extraction (PHWE) method to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Li et al [ 8 ] evaluated the DPPH radical scavenging potential and ferric-reducing ability of eight different Phyllostachys species and found that the leaves of P. pubescens resulted the most active, whereas among the sheath the strongest antioxidant potential was observed in the golden thread moso bamboo. More recently, Cao et al [ 42 ] investigated the impact of the extraction procedure on the recovery of bioactive compounds using Bambusa chungii culms processing waste, as well as its influence on antioxidant activity. The best extraction conditions were found at a temperature of 160 °C and with a solvent ratio of 1:30 g/mL for 14 min.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [ 8 ] evaluated the DPPH radical scavenging potential and ferric-reducing ability of eight different Phyllostachys species and found that the leaves of P. pubescens resulted the most active, whereas among the sheath the strongest antioxidant potential was observed in the golden thread moso bamboo. More recently, Cao et al [ 42 ] investigated the impact of the extraction procedure on the recovery of bioactive compounds using Bambusa chungii culms processing waste, as well as its influence on antioxidant activity. The best extraction conditions were found at a temperature of 160 °C and with a solvent ratio of 1:30 g/mL for 14 min.…”
Section: Resultsmentioning
confidence: 99%